“Diopter or Mirror, and image of human life in this world” (Vievis, 1612): on the history of orthodox literature of the early 17th century - Margarita Korzo (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Published in the town of Vievis by Vilna Orthodox fraternity, “Dioptra ili Zertsalo” (Diopter or Mirror, and Image of Human Life in this World, 1612) is an interesting example of moral-ascetic literature of the early 17th century. Reprinted several times before the end of the century, this book was also popular among Old Believers. “Dioptra” of Vievis had long been identifi ed with “Dioptra” (The Mirror) of Phillip the Recluse; it was also considered to be a translation of an unknown Greek text. This article examines the statement made by Cassian Sakowicz in “Desiderosus” (Cracow, 1625) that “Dioptra ili Zertsalo” is a translation of the Latin version of “Libro de la vanidad del mundo” (Toledo, 1562) written by the Spanish Franciscan Diego de Estella. The article also studies the functional role of numerous rhyming fragments in “Dioptra ili Zertsalo”; the question is raised as to which fragments and quotations from ancient literature and theological works were included in “Dioptra ili Zertsalo” through its Latin source; another question is about sources of erudition of the Vievis “Dioptra” author, Abbot Vitaliy. Besides, the article analyses the so-called “library resource” of the first preface to “Dioptra ili Zertsalo”, compiled by its publishers. A hypothesis is suggested about the familiarity of Vilna Orthodox fraternity’s members with comments on the “Four Books of Sentences” by Peter the Lombard, written in 1586 by the professor of the Cracow Academy, the Italian Franciscan Hannibala Rosselli. The “case” in question is part of a larger problem, i.e. that of the sources of erudition of the Orthodox writers and authors of the early 17th century in the Polish-Lithuanian Commonwealth.